2007
DOI: 10.1577/m06-151.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Management Strategy to Control the Spread of Myxobolus cerebralis in a Lower Columbia River Tributary

Abstract: In October 2001, Myxobolus cerebralis, the myxozoan parasite that causes salmonid whirling disease, was detected in juvenile rainbow trout Oncorhynchus mykiss from a private hatchery that received water from Clear Creek, a tributary of the Clackamas River, Oregon. The Oregon Department of Fish and Wildlife closed the surface water portion of the hatchery in March 2003 and initiated a monitoring program to evaluate the success of the closure in containing further parasite spread. From 2002 to 2005, rainbow trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Because our methods of detection have proven effective in other parts of Alaska (south-central) as well as in other studies (Arsan, 2006;Bartholomew et al, 2007), we think this study accurately represents the relative abundance of T. tubifex in the areas sampled. It is possible that more extensive surveys may detect T. tubifex in southeastern Alaska.…”
Section: Tubifex Tubifex Surveymentioning
confidence: 78%
See 1 more Smart Citation
“…Because our methods of detection have proven effective in other parts of Alaska (south-central) as well as in other studies (Arsan, 2006;Bartholomew et al, 2007), we think this study accurately represents the relative abundance of T. tubifex in the areas sampled. It is possible that more extensive surveys may detect T. tubifex in southeastern Alaska.…”
Section: Tubifex Tubifex Surveymentioning
confidence: 78%
“…In reference to the dense populations of worms frequently found where organic enrichment is high, the term sludge worms is often used to describe T. tubifex. Researchers have found the worms in hatchery settling ponds but not in the surrounding stream sediments (Allen and Bergersen, 2002;Bartholomew et al, 2007). Fish hatchery worms were tallied separately in this study (Table II), because settling ponds are independent from the main creek channel, and they are not representative of T. tubifex abundance in the wild.…”
Section: Tubifex Tubifex Surveymentioning
confidence: 97%
“…Furthermore, because of their relatively high worm densities, disturbed environments are more likely to have worm populations at risk of infection. For example, Bartholomew et al (2007) identified a hatchery with a large worm population that propagated M. cerebralis, compared with the adjoining creek with few T. tubifex and no detectable parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of the parasite life cycle in tributaries of the lower Columbia River (the Deschutes and Willamette River basins) has occurred only sporadically, after introduction by infected adult salmonids that stray during their return to the upper Columbia River tributaries (Bartholomew and Reno, 2002;Engelking, 2002;Bartholomew et al, 2007;Zielinski, 2008). In the Deschutes River basin, M. cerebralis was detected in 1987 in stray steelhead trout at Warm Springs National Fish Hatchery and later in stray steelhead and Chinook salmon at Round Butte Hatchery (Engelking, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation